Determinants of export behaviour of German business services companies - Alexander Eickelpasch; Alexander Vogel (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The determinants of export behaviour at firm level have been widely investigated for manufacturing companies. By contrast, what has remained largely neglected is a detailed investigation in the service sector. As aggregate statistics show, international trade in services has grown significantly over the last few years. However, it is unclear why some companies export and others do not. This paper presents some initial results about the German business services sector at firm level. Using a unique panel dataset of enterprises from the business services sector (transport, storage and communication, real estate, renting and business activities) for the years 2003 to 2005, we analysed the impact of several firm-specific characteristics such as size, productivity, human capital, experience on the national market in Germany, etc. on the firms' export performance. Further, we used the pooled fractional probit estimator, recently introduced by Papke & Wooldridge, an approach that considers both the special nature of the export intensity variable and in addition unobserved time-invariant characteristics. When there is no control for fixed enterprise effects the overall results are in line with previous studies. When there is a control for unobserved heterogeneity, the positive effects of productivity and human capital disappear, indicating that these variables are not per se positively related to export performance, but rather to time-constant characteristics that are unobserved. Size and product diversification still have a positive and significant effect.
Keywords: F14; F23; L80; 330; Business services sector; export behaviour; firm performance; Unternehmensdienstleistung; Export; Internationaler Dienstleistungsverkehr; Unternehmensentwicklung; Deutschland